2017
DOI: 10.1123/ijsnem.2016-0321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbohydrate Ingestion and Carbohydrate Mouth Rinse on Repeat Sprint Performance

Abstract: The purpose of this investigation was to examine to the influence of carbohydrate ingestion (CHOI) and carbohydrate mouth rinse (CHOR) on acute repeat maximal sprint performance. Fourteen healthy males (age: 21.7 ± 1.8 years, mass: 82.3 ± 12.3 kg) completed a total of five 15-s maximal repeat sprints on a cycle ergometer against 0.075 kg ・ kg body mass each separated by 4 min of active recovery. Subjects completed four experimental trials and were randomly assigned one of four treatments: (1) CHOI, (2) CHOR, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
2
23
1
Order By: Relevance
“…In the current study, both peak (PPO) and mean power outputs (MPO) systematically declined with each interval, relative to the previous interval, which is in agreement with observations from previous SIE studies [18,20,24,25,28]. Bogdanis et al [25] demonstrated that following performance of a second consecutive 30 s sprint with either 1.5, 3 or 6 min of passive recovery, neither of these recovery periods were sufficient to maintain PPO or MPO compared to the first sprint.…”
Section: Potential Impact Of Cho On Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, both peak (PPO) and mean power outputs (MPO) systematically declined with each interval, relative to the previous interval, which is in agreement with observations from previous SIE studies [18,20,24,25,28]. Bogdanis et al [25] demonstrated that following performance of a second consecutive 30 s sprint with either 1.5, 3 or 6 min of passive recovery, neither of these recovery periods were sufficient to maintain PPO or MPO compared to the first sprint.…”
Section: Potential Impact Of Cho On Performancesupporting
confidence: 92%
“…However, such recommendations have been made in the context of continuous, time-trial or intermittent team sport type performance tests, and have not considered repeated, maximal efforts of a shorter total duration. Each of the three aforementioned SIE studies reporting an ergogenic effect of CHO ingestion employed a variety of different maximal SIE protocols, including 5 × 15 s maximal sprints interspersed with 4 min of active recovery [20], 6 × 5 s maximal sprints interspersed with 25 secs passive recovery [18], and 10 sets of 5 × 4 s sprints with 20 s active recovery between sprints, and 2 min between sets [19]. Therefore, the total session durations of these protocols were 17.25 min, 2.5 min and 34.66 min respectively, with extremely low actual exercise durations of 75 s, 30 s and 200 s, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that consuming even small amounts of carbohydrate (16 g per hour) can improve exercise performance, but the optimal dose and timing are still under investigation. Emerging evidence also suggests that a mouth rinse with a carbohydrate‐containing fluid has greater effects on athletic performance compared with a non‐carbohydrate‐containing mouth rinse 25 27 . In an athlete who is unable to retain enteral nutrition (EN), it may be beneficial to have the athlete take a drink of a carbohydrate‐containing liquid and swish and spit out the liquid.…”
Section: Assessment and Energy Requirements For The Athlete Receiving Pnmentioning
confidence: 99%
“…Among nutritional strategies, Carbohydrate (CHO) manipulation has been widely studied. It has been used as an ergogenic resource to improve performance in various sports [4][5][6]. Over the years, the effects of CHO on long-term exercise performance [7,8] and on high-intensity exercises [9] have become increasingly popular.…”
Section: Introductionmentioning
confidence: 99%